Determining Factors for Work Readiness of Students in The Management Program at Muhammadiyah University of Purworejo - Qonitatun Mardliyah; Esti Margiyanti Utami; Dedi Runanto (IECON: International Economics and Business Conference, 2025)
The study explores the impact of soft skills, hard skills, and internship experience on the employability of Management students at Muhammadiyah University of Purworejo's Faculty of Economics. The background of this research is the high unemployment rate among university graduates in Indonesia, indicating a gap in graduates’ readiness to enter the workforce. In the current era of globalization and digital transformation, students are required to demonstrate not only academic excellence but also essential non-academic skills like communication, leadership, and problem-solving, as well as gain hands-on experience through internships. This quantitative research adopts a survey approach, with a purposive sample of 100 students. Data were collected using questionnaires and analyzed using SPSS with multiple linear regression. The analysis confirms that work readiness is positively and significantly shaped by students’ soft skills, hard skills, and internship involvement.Soft skills exert the strongest effect (52.8%), followed by hard skills (27.9%) and internship experience (24.4%), all with a significance level of < 0.001. The R-Square value of 0.919 indicates that these three variables collectively explain 91.9% of the variation in work readiness. These results highlight the crucial role of integrating both academic and practical skill development to enhance graduate employability.